Identifying Student Misconceptions in Buffer Solution Concepts Using Mental Model-Based Diagnostic Test - Ramlawati*, Ramlawati; Rosadi, Husna Hadi; Hussain, Halimah; Sari, Nur Indah; Ilmi, Nurul (Jurnal IPA & Pembelajaran IPA, 2025)
Chemistry learning often faces challenges in the form of misconceptions, especially in buffer solution material, which is abstract because it involves the concepts of chemical equilibrium and acid-base properties. This study aims to produce information about the use of diagnostic tests with the Interview-About-Event method in exploring students' mental models on buffer solution material. The research method used was descriptive qualitative on 9 grade XII students at a high school in Makassar City using in-depth interviews that asked students to explain the phenomena given. Data collection was carried out using research instruments in the form of a diagnostic test and semi-structured interviews. The answers of each student were mapped to obtain a profile of their mental models. The results showed that the studChemistry learning often presents challenges in the form of misconceptions, particularly concerning buffer solutions. This material is abstract as it involves the concepts of chemical equilibrium and acid-base properties. This study aims to provide information on using diagnostic tests with the interview-about-event method to explore students' mental models. The research employed a descriptive qualitative method with nine 12th-grade students from a high school in Makassar City. Data was collected through in-depth interviews that asked students to explain given phenomena, utilizing research instruments in the form of a four-tier diagnostic test and semi-structured interviews. The answers of each student were mapped to obtain a profile of their mental models. The results indicated that students' mental models revealed diversity in their responses, especially at the submicroscopic level. Their mental models tended to be simple, incomplete, and macroscopic, characterized by misconceptions such as considering equilibrium shifts to be separate from the direct reactions of buffer components, misunderstandings in using arrows for partial and complete ionization, incorrect definitions of acids, and misconceptions about buffer solutions neutralizing pH or causing pH changes. The diversity and consistency of these misconceptions underscore the importance of a pedagogical approach focused on deep conceptual understanding and the integration of multiple levels of chemical representationents' mental models revealed diversity in their answers, especially at the submicroscopic level. Their mental models tended to be simple, incomplete, and macroscopic, characterized by misconceptions such as considering equilibrium shifts to be separate from the direct reactions of buffer components, misunderstandings in the use of arrows for partial and complete ionization, incorrect definitions of acids, and misconceptions about buffer solutions in neutralizing pH or causing pH changes. The diversity and consistency of these misconceptions emphasize the importance of a pedagogical approach focused on deep conceptual understanding and the integration of multiple levels of chemical representation